Novel citrus hybrids incorporating Australian lime genetics: development of HLB-tolerant citrus rootstocks and physiological changes in ‘Valencia’ sweet orange scions - Mahmoud, Lamiaa M.; Dutt, Manjul (Frontiers in Plant Science, 2025)
Citrus greening disease, or Huanglongbing (HLB), is the most destructive disease affecting citrus crops worldwide. All commercially cultivated citrus varieties are highly susceptible to HLB, and currently, no effective treatments exist. Several Australian lime species have demonstrated significant HLB tolerance, making them promising candidates for developing HLB-tolerant rootstocks and scions through conventional breeding and biotechnological approaches. Herein, we report the successful development of HLB-tolerant citrus hybrids via integrating Australian lime genetics using traditional breeding methods and protoplast fusion techniques. To test the HLB tolerance of these hybrids as rootstocks, they were clonally propagated through cuttings and divided into two groups: one grafted with CaLas-free ‘Valencia’ sweet orange budwood and the other grafted with CaLas-infected ‘Valencia’ budwood. The performance of these hybrids was compared to similar CaLas-infected and free 'Valencia' budded onto Swingle rootstock. Total DNA was isolated from the ‘Valencia’ leaves at 6, 12, 18, and 24 months post-grafting to assess CaLas titers using quantitative PCR. After two years, significantly higher Ct values (ranging from 29.11 to 35.00) was observed in ‘Valencia’ trees grafted onto the experimental hybrids than in those grafted onto Swingle, which presented a Ct value of 22.25 ± 1.11. Compared with other hybrids, the mandarin (UF304) × finger lime hybrid (MFL1-98) and pummelo × finger lime hybrid (PFL2-61) exhibited improved graft-take, enhanced growth, and lower CaLas titers. Additionally, we analyzed the biochemical and molecular changes in the leaves of ‘Valencia’ grafted onto these Australian lime-derived hybrids. Biochemical analyses revealed significant alterations in chlorophyll content, starch accumulation, and levels of phenolic and flavonoid compounds. These results demonstrate the practical benefits of using Australian lime-derived hybrids as rootstocks to increase HLB tolerance in citrus, offering a promising approach for the sustainable management of HLB in commercial citrus production.